2018
DOI: 10.1097/ta.0000000000002043
|View full text |Cite
|
Sign up to set email alerts
|

The volume-outcome relationship in severely injured patients: A systematic review and meta-analysis

Abstract: Systematic review and meta-analysis, level III. Systematic review registration number: PROSPERO registration ID CRD42017056729.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 46 publications
0
62
2
1
Order By: Relevance
“…This study aimed to evaluate whether there was an association between hospital volume and outcomes among severely injured patients in Major Trauma Centres. Despite the large variation in volume of the included MTCs, no relationship between hospital volume and outcome of severely injured patients was found, contrary to current beliefs [5]. Small between-centre differences for in-hospital mortality were found which suggests comparable outcomes between MTCs.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…This study aimed to evaluate whether there was an association between hospital volume and outcomes among severely injured patients in Major Trauma Centres. Despite the large variation in volume of the included MTCs, no relationship between hospital volume and outcome of severely injured patients was found, contrary to current beliefs [5]. Small between-centre differences for in-hospital mortality were found which suggests comparable outcomes between MTCs.…”
Section: Discussioncontrasting
confidence: 81%
“…The current study showed no evidence for the volume-outcome relationship in severely injured patients treated in MTCs. This is in contrast with a recently published systematic review and meta-analysis which found a beneficial effect for high volume centres [5]. However, most of these studies included both MTCs and non MTCs, so a potential volume effect could be biased by other factors.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Adjusted odds ratios (ORs) and their 95% confidence intervals (CIs) were obtained after adjusting for age (16-39 vs. 40-64 vs. 65≤); gender; mechanism of injury (blunt or others); transfer from outside hospitals; ISS (≤8 vs. 9-15 vs. 90mmHg≤ on arrival); Glasgow Coma Scale score (≤8 vs. 9-15); presence or absence of emergency surgical or hemostatic intervention (craniotomy, thoracotomy, laparotomy, or angioembolization); and type of institution (high vs. low volume centers). Because outcomes would be better at the high-volume centers, an additional analysis was conducted by dividing the patients into two groups; high volume centers (≥1,200 cases with ISS≥9 registered for 12 years) and low volume centers (<1,200 cases with ISS≥9 registered for 12 years) [18]. A subgroup analysis was also conducted, stratifying patients with or without shock and the type of national meeting.…”
Section: Methodsmentioning
confidence: 99%